Penggunaan Metode Eksperimen Berbasis Sains dalam Meningkatkan Kreativitas Anak Usia Dini di RA Roihanul Jannah - Robiyatul Adawiyah; Mukhlis Mukhlis; Zulpina Zulpina (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2025)
This study investigates the use of science-based experimental methods to enhance creativity in early childhood at RA Roihanul Jannah. The research involved 31 students actively engaging in science learning through experiments. A qualitative approach was adopted, focusing on Group B teachers and the principal as informants. Data were collected through observation, interviews, and documentation from July to August 2024. The findings indicate that the experimental method effectively promotes scientific understanding, curiosity, and problem-solving skills among children. It also enhances fine and gross motor skills through hands-on activities. However, challenges include the need for specific materials and time constraints. The study concludes that incorporating experimental methods in early childhood education significantly fosters creativity and engagement in science.